Case report: Efgartigimod treatment in two pediatric patients with chronic inflammatory demyelinating polyneuropathy - Ran, Yanping; Wu, Wenlin; Hou, Chi; Zhu, Haixia; Wu, Wenxiao; Chen, Zongzong; Ma, Xuexia; Mo, Xiaolan; Deng, Houliang; Gao, Yuanyuan; Li, Xiaojing (Frontiers in Immunology, 2026)
BackgroundChronic inflammatory demyelinating polyneuropathy (CIDP) is the most common chronic immune-mediated polyneuropathy. Early and effective immunomodulatory treatment is essential to prevent long-term disability. Efgartigimod, a human IgG1 Fc fragment, has recently been approved for adult CIDP, but its safety and efficacy in pediatric CIDP remain unstudied. We retrospectively analyzed two pediatric patients with CIDP who received efgartigimod treatment.Case reportAge at onset was 1.5 and 3.4 years; disease duration before efgartigimod was 1.5 and 3.2 years; and age at initiation was 3.0 and 6.6 years. Prior treatments included corticosteroids, maintenance intravenous immunoglobulin, mycophenolate mofetil, and rituximab in one patient, and corticosteroids plus maintenance intravenous immunoglobulin in the other. Both initiated efgartigimod due to uncontrolled relapses. At final follow-up (8 months), both showed improvement in Medical Research Council (MRC) sum scores and Inflammatory Neuropathy Cause and Treatment (INCAT) scores. One patient experienced a single relapse; the other remained relapse-free. Two mild, self-limited adverse events occurred: upper respiratory tract infection in one and transient alanine aminotransferase elevation in the other.DiscussionThis is the first report of efgartigimod use in pediatric patients with CIDP. Efgartigimod was generally well tolerated, and some clinical improvements were observed in this population. However, given the small sample size, these findings should be considered preliminary and require confirmation in larger, prospective studies.